Elucidation of molecular pathways responsible for the accelerated wound healing induced by a novel fibrous chitin dressing. (11th October 2019) - Zhong, Zibiao; Huang, Yao; Hu, Qianchao; He, Weiyang; Duan, Bo; Yan, Xiaomin; Yang, Zhenjie; Liang, Wenjin; Liu, Zhongzhong; Peng, Zhonghua; Wang, Yanfeng; Zhang, Lina; et al.
Abstract : Fibrous chitin dressing (FCD) prepared from a NaOH-urea aqueous solution of chitin via a physical process was used to study its effect on wound healing using a full-thickness cutaneous wound model in rats and mice. Abstract : Fibrous chitin dressing (FCD) prepared from a NaOH-urea aqueous solution of chitin via a physical process was used to study its effect on wound healing using a full-thickness cutaneous wound model in rats and mice. It was demonstrated that wounds in rats covered with the FCD showed faster collagen (especially type I collagen) growth and speedier healing than those with Gauze (12 days versus 16 days). The ability of FCD to promote wound healing was also observed on wild-type (WT) mice. For MyD88-knockout mice, however, FCD displayed no beneficial but an adverse effect on wound healing: the healing time for wounds treated with FCD was even longer than those treated with gauze. Importantly, in vivo studies indicated that FCD-treated mice, compared to gauze-treated ones, exhibited markedly higher expressions of MyD88, IKBα, TGF-β, P-TβR II, TβR II and P-Smad2/3 in wild-type mice. For MyD88 knockout mice, however, the expressions of those molecules were inhibited and lowered in FCD-treated ones than those treated with gauze. In vitro studies confirmed that chitin increased the expression of TGF-β, P-TβRII and P-Smad2/3 while the expressions of those molecules were significantly inhibited with CD14 antibody ( p < 0.05). These results indicated that FCD accelerated wound healing through a MyD88-dependent pathway, followed by a TGF-β/Smad pathway. This work not only demonstrated the superior wound healing effect of chitin-derived dressing, but also provided for the first time the underlying molecular mechanism, further establishing chitin as an important biomedical material for potential clinical applications.